1976
DOI: 10.1002/j.1537-2197.1976.tb11851.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Adaptations of Salt Marsh Grass, Distichlis Spicata (Gramineae), and Environmental Factors Affecting Its Growth and Distribution

Abstract: Salt grass is an important pioneer plant in early stages of succession. The sharp-pointed rhizomes with numerous epidermal silica cells, and the aerenchymatous network of the rhizome, leaf sheath, and roots facilitate development of the plant in heavy clays, shales, and inundated soils. In salt marshes of southern Utah, salt grass contributes to a hummock-building process that favors localized removal of salts by capillary action and evaporation. This process provides a narrow strip of soil that is favorable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

1980
1980
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…Further increase in concentration of NaCl caused an obvious decrease in the amount of secreted fluid (Batanouny, Hassan & Fahmy, 1992). Hansen et al (1976) measured salt secretion of Distichlis spicata by the rinsing method, and recorded a diurnal rhythm with more salts being secreted during the night. By contrast, Scholander et al (1962) and Hill & Hill (1976) concluded that the daily changes in the secretion rates seemed to follow the diurnal rhythm of transpiration.…”
Section: mentioning
confidence: 99%
“…Further increase in concentration of NaCl caused an obvious decrease in the amount of secreted fluid (Batanouny, Hassan & Fahmy, 1992). Hansen et al (1976) measured salt secretion of Distichlis spicata by the rinsing method, and recorded a diurnal rhythm with more salts being secreted during the night. By contrast, Scholander et al (1962) and Hill & Hill (1976) concluded that the daily changes in the secretion rates seemed to follow the diurnal rhythm of transpiration.…”
Section: mentioning
confidence: 99%
“…al. 1959) and herbivores (Hansen et al 1976;Hunt et al 2008). Also, depending on the type and location of deposition, it is an important taxonomic characteristic (Metcalfe 1969;Dahlgreen & Cliff ord 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Hansen et al (1976) observaron esta característica en plantas de Distichlis que crecieron en suelos saturados.…”
Section: Discussionunclassified
“…Se observa un gran aumento de la pubescencia en hoja a -0,4 MPa, conjuntamente con el aumento del número de lagunas en la corteza de la raíz y el aumento relativo de la corteza del tallo. Estos efectos son característicos de medios desecantes (Fahn 1974, Hansen et al 1976. Quizás esta sal le produce mayor perjuicio al vegetal y como resultado un efecto haloxeromórfico.…”
Section: Discussionunclassified